2011
DOI: 10.1198/jasa.2011.tm10332
|View full text |Cite
|
Sign up to set email alerts
|

Independent Component Analysis Involving Autocorrelated Sources With an Application to Functional Magnetic Resonance Imaging

Abstract: Independent component analysis (ICA) is an effective data-driven method for blind source separation. It has been successfully applied to separate source signals of interest from their mixtures. Most existing ICA procedures are carried out by relying solely on the estimation of the marginal density functions, either parametrically or nonparametrically. In many applications, correlation structures within each source also play an important role besides the marginal distributions. One important example is function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…For temporal ICA, this can be implemented by using time series models to account for the source serial correlations. Indeed, Lee et al (2011) has reported that there is noticeable improvement over the marginal density based ICA procedures. It will be important to see if the same will hold for the above spatial ICA approach using tensor products of splines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For temporal ICA, this can be implemented by using time series models to account for the source serial correlations. Indeed, Lee et al (2011) has reported that there is noticeable improvement over the marginal density based ICA procedures. It will be important to see if the same will hold for the above spatial ICA approach using tensor products of splines.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that we should also provide a sensitivity and specificity analysis of the activated spatial locations as described in Lee et al (2011), where popular methods such as Infomax and fastICA were shown to have a higher false-positive/nagative rate. This implies that brain activation should be studied more carefully, and one should avoid using methods that tend to yield false activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For simplicity, we focus on the case M = N for the rest of the manuscript. Many algorithms are available for instantaneous mixtures based on different independence measurements, such as high-order statistics [3], information theoretic measurements [4-6], canonical correlations in a reproducing kernel Hilbert space [7], maximum likelihood [8-11], characteristic function [12, 13] and the Whittle likelihood [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Although identifying mixing models is critical, our literature review showed little research regarding the effects of misspecified ICA models, excepting cases of instantaneous mixing. For example, [14] has indicated that most marginal independence measure based approaches, which intrinsically assume temporal independence of sources, fail to separate autocorrelated sources. Model identification becomes even more difficult in convolutive mixing cases without proper constraints when the sources are autocorrelated.…”
Section: Introductionmentioning
confidence: 99%